Faktor Hambatan Penerapan Imunisasi Dasar Anak di Indonesia - Fiorentina Nova; Fransiska Ompusunggu; Lia Kartika (Universitas Malahayati, 2023)
ABSTRACT Human resources with good health status are essential for a nation's development. One of the preventive efforts to reduce morbidity and mortality in children caused by infectious diseases is through primary immunization. The survey results regarding implementing basic immunization in Indonesia in 2019 have decreased compared to the previous year. To reveal the factors that hinder basic immunization activities for children in Indonesia. A literature search using the National Library of Indonesia, PubMed, and Google Scholar with the keywords